Review of the Oriental genus Neoperlops Banks, 1939 (Plecoptera: Perlidae) - Mo, Raorao; Wang, Guoquan; Li, Weihai; Murányi, Dávid (Zootaxa, 2020)
A new species of the Oriental Perlidae genus Neoperlops Banks, 1939, Neoperlops triangulatus sp. nov. is described from Guangxi Zhuang Autonomous Region of southern China. Neoperlops gressitti Banks, 1939 is redescribed, and recorded from Guangxi Zhuang Autonomous Region for the first time. Neoperlops huanghuye (Chen, 2020) comb. n., recently described from Fujian Province from southeastern China, is transferred from Phanoperla Banks, 1938. The six species of the genus are classified in two groups of morphologically similar species.